2001
DOI: 10.1046/j.1439-037x.2001.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Ratios and Crop Performance: II. Effects of Interactions amongst Vanadium, Phosphorus, Magnesium and Calcium on Soybean Yield

Abstract: Because vanadium (V) is easily reduced to a cationic form within plant cells, data from resin‐extraction of soil were analysed for evidence of interactions between V and the resin‐extractable concentrations of magnesium (Mg) and calcium (Ca) on soybean seed yield. Three varieties, 9091, 9061 and 704, were grown over a 3‐year period in a corn–soybean–wheat rotation. Surface soil samples (0–15 cm) were extracted with ion‐exchange resins, extracts were analysed by inductively coupled plasma methods (ICP), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Moreover it is confirmed that vanadium inhibits and impairs the phosphate metabolizing enzymes like phosphatases, lyases, synthases, ATPases etc. (Ding et al, 1994;Stankiewicz et al, 1995;Olness et al, 2001). The vanadate interferes during metabolic processes involving phosphate in cytoplasm of the cell (Bowman, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover it is confirmed that vanadium inhibits and impairs the phosphate metabolizing enzymes like phosphatases, lyases, synthases, ATPases etc. (Ding et al, 1994;Stankiewicz et al, 1995;Olness et al, 2001). The vanadate interferes during metabolic processes involving phosphate in cytoplasm of the cell (Bowman, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The vanadate interferes during metabolic processes involving phosphate in cytoplasm of the cell (Bowman, 1983). Vanadium is a potent enzymes inhibitor and can be used to characterize the enzymes involving in phosphate transfer (Olness et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression analyses showed very different responses of two maize hybrids to the RE chemical environment. The response of hybrid 2292 to increased Mg relative to Ca was similar to the response of a soybean variety to the same molar ratio (Olness et al 2001). It is not clear, however, that the Mg : (Mg + Ca) effect represents a direct interaction of Mg with the plant and it is entirely possible that increased relative Mg concentrations may be enhancing auxiliary rhizosphere biota in both the soybean and maize seed yield results.…”
Section: Resultsmentioning
confidence: 53%
“…However, H 2 VO À 4 is easily reduced by a variety of reductants to the vanadyl (VO 2+ ) form within the cell and both ions readily coordinate with a number of functional groups (see Crans and Tracey 1998). Internal cellular reduction of H 2 VO À 4 to VO 2+ led us to speculate on the possibility of interactions with calcium (Ca 2+ ) and magnesium (Mg 2+ ) in a set of observations from soybean; an analysis of the data showed a strong seed yield increase as the Mg 2+ : (Mg 2+ + Ca 2+ ) molar ratio increased for an iron-chlorosis resistant variety (Olness et al 2001).…”
Section: Introductionmentioning
confidence: 98%